Predictors of liver histological changes and a sustained virological response to peginterferon among chronic hepatitis B e antigen‐positive patients with normal or minimally elevated alanine aminotransferase levels. Issue 7 (16th February 2017) - Chen, J.; Xu, C. R.; Xi, M.; Hu, W. W.; Tang, Z. H.; Zang, G. Q.
Summary: A proportion of chronic hepatitis B patients with normal or only minimally elevated alanine aminotransferase (ALT) levels display significant histologic changes and would benefit from antiviral therapy. We aim to evaluate the histologic abnormalities seen in these patients and then determine which of them would most likely respond to peginterferon therapy. One hundred and thirteen hepatitis B e antigen (HBeAg)‐positive patients with a normal or minimally elevated ALT level and moderate‐to‐severe histologic changes in their liver tissue were selected to receive peginterferon monotherapy and participate in a follow‐up analysis. A multiple logistic regression analysis indicated that increasing age ( P =.049) and lower hepatitis B virus (HBV) DNA levels ( P =.038) were associated with significant histological abnormalities in patients with a normal or minimally elevated ALT. Our predictive model which incorporated HBeAg testing at treatment week 12 combined with hepatitis B surface antigen (HBsAg) testing at treatment week 24 was able to identify which patients with a normal ALT level would achieve a sustained virological response (SVR) (positive predictive value [PPV]: 66.7%, negative predictive value [NPV]: 90.0%). Lower HBsAg and HBeAg levels at treatment week 24 were associated with a SVR in patients with a minimally elevated ALT level (PPV: 100.0%, NPV: 100.0%). A liver biopsy and antiviral therapy should be strongly considered when treating HBeAg‐positive patients with a normal or minimally elevated ALT level, low HBV DNA level, and aged >35 years. On‐treatment quantification of combined HBsAg and HBeAg test results may be useful for predicting a SVR to peginterferon monotherapy in these patients.